Термохимический синтез малощелочного субмикрокристаллического корунда, модифицированного изоморфными атомами - А. А. Ханамирова; А. Р. Адимосян; Л. П. Апресян; Л. А. Чилингарян (ՀՀ ԳԱԱ հրատ.)
Разработан эффективный одностадийный термохимический способ получения из крупнозернистого технического гидроксида алюминия реакционноспособного малощелочного субмикрокристаллического корунда, модифицированного атомами Mg, Mn, Zn, Ti, Si, Ag. Հետազոտվել է կոմպլեքսային հանքայնարարների և բարեփոխիչների ներկայությամբ ջերմաքիմիական ակտիվացման պայմանների ազդեցությունը Al(OH)3-ի փուլային բաղադրության, անհավասարակշիռ ակտիվ կառուցվածքի առաջացման, մանրացվածության փոփոխման վրա: It has been studied the influence of complex mineralisers (Al(NO3)3 ּ 9H2O, Al(C2H3O2)3, AlF3, (NH4)2CO3, NH4F, B2O3), modifiers ( Mg-, Mn-, Zn-, Ag-, Ti-, Si- - various compounds) and conditions of one-step phase thermochemical decomposition process on the phase composition changes, on the change of dispersity, on the migration of alkaline ions from the volume of particles to their surface, on formation of non-equilibrium active structure, kinetics of thermal decomposition of aluminium hydroxide, its full phase transformation into α-Al2O3.
Keywords: Inorganic Chemistry